A Novel Mechanism of Doxorubicin Resistance and Tumorigenesis Mediated by MicroRNA-501-5p-Suppressed BLID - Yun-chao Xu; Xu Liu; Min Li; Yan Li; Chun-yan Li; Ying Lu; Jaceline Sanches; Lu Wang; Yue Du; Li-min Mao; Si-bo Zuo; Hui-ting Liu; et al. (Elsevier, 2018)
Doxorubicin is a widely used anthracycline-based anti-tumor agent for both solid and liquid tumors. Mounting evidence has demonstrated that microRNAs (miRNAs) are involved in chemoresistance and tumorigenesis. However, the roles of microRNA-501-5p (miR-501) in doxorubicin resistance and gastric cancer cell proliferation and invasion are still not fully understood. In this study, we identified that BLID (BH3-like motif-containing protein, cell death inducer) was directly regulated by miR-501 at the post-transcriptional level in multiple gastric cancer cell lines. Endogenous miR-501 was higher, whereas BLID was lower, in doxorubicin-resistant gastric cancer SGC7901/ADR cells compared with their parental SGC7901 cells. miR-501 suppressed gastric cancer cell apoptosis, induced resistance to doxorubicin, and enhanced cell proliferation, migration, and invasion. Subcutaneous injection of miR-501 lentivirus-infected SGC7901 cells resulted in rapid growth of xenograft tumors and resistance to doxorubicin treatment, unlike injection of negative miRNA lentivirus-infected SGC7901 cells. This is achieved at least partially by directly targeting BLID and subsequent inactivation of caspase-9 and caspase-3 and phosphorylation of Akt. Taken together, miR-501 induces doxorubicin resistance and enhances the tumorigenesis of gastric cancer cells by suppressing BLID. miR-501 might be a potential target for doxorubicin resistance and gastric cancer therapy. Keywords: microRNA-501-5p, chemoresistance, doxorubicin, BLID, gastric cancer